Pengaruh Return on Asset, Return on Equity, Debt to Equity Ratio, dan Price Earnings Ratio terhadap Return Saham: Studi Empiris pada Perusahaan Sektor Property & Real Estate yang Tercatat di Bursa Efek Indonesia periode 2018 – 2023 - Heryaman, Dony; Anasta, Lawe (Penerbit Goodwood, 2024)
Purpose: This research aims to determine the effect of Return on ssets (ROA), Debt to Equity Ratio (DER), and Price to Earning Ratio (PER) on stock returns in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2018 - 2023 period. Research methodology: The sampling method uses a purposive sampling method by applying certain characteristics so that a total sample of 9 companies is obtained. The test uses multiple linear regression analysis to test the independent variables Return on Assets (ROA), Debt to Equity Ratio (DER), and Price to Earning Ratio (PER) on the dependent variable, namely stock returns. Results: Based on the results of the partial t-test, it shows that the ROA and DER variables have a partial effect on stock returns. Meanwhile, ROE and PER have no partial effect on stock returns. Meanwhile, the results of the F-simultaneous hypothesis test show that return on assets, return on equity, debt to equity ratio, and price earnings ratio have a simultaneous effect (together) on stock returns with a significant value of 0.00<0.05. Limitations: This study is limited to 9 companies in the property and real estate sector and the 2018-2023 period, so the results may not fully represent the entire industry or broader market conditions. Contribution: This study aims to provide practical insights for companies in enhancing stock returns and attracting investors, while offering investors key financial ratios for informed decision-making. It also serves as a reference for future research.